The Association of Meningitis with Postoperative Cerebrospinal Fluid Fistula - Allen, Kyle P.; Isaacson, Brandon; Kutz, J. Walter; Purcell, Patricia L.; Roland, Peter S. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective To determine the risk factors for and the clinical course of postoperative meningitis following lateral skull base surgery and to determine its relationship to cerebrospinal fluid (CSF) fistula.Patients Patients undergoing lateral skull base surgery between July 1999 and February 2010 at an academic tertiary referral center. All subjects had culture-proven meningitis or suspected bacterial meningitis in the postoperative period. Medical records were compared with the lateral skull base patients who did not develop meningitis.Results Of 508 procedures, 16 patients developed meningitis (3.1%). The most common diagnosis was acoustic neuroma in 81.3%; 68.8% of patients had a CSF leak prior to onset of meningitis, and 50% received a lumbar drain. The median time from surgery to the onset of meningitis was 12 days with a range of 2 to 880 days. The relative risk of developing meningitis in the setting of postoperative CSF fistula is 10.2 (p <0.0001). No meningitis-associated mortality was observed.Conclusions Postoperative meningitis occurred in a small number of patients undergoing lateral skull base surgery. A postoperative CSF fistula leads to an increased risk of meningitis by a factor of 10.2.
Keywords: meningitis; postoperative meningitis; acoustic neuroma